Types of Modality in News Item is Used in the Texts News in the Jakarta Post Newspaper - T. Aldilla Syahira; T. Silvana Sinar; Masdiana Lubis (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research aimed to find out types of modality  and  to  explain  how  the  most  dominant types of modality in news item is used in  the  texts  news  in  The  Jakarta  Post  newspaper. This research was conducted by using corpus analysis as the appropriate tool to analyze the online written text.  The  data  were  taken  from  the  source  of  Jakarta  Post  newspaper which published online from the 1st August until 31th December  2019.  The sources varied in four themes i.e. politic, education, sports and economic news.  As a result, the researcher found 2 types of modality there are modalization and modulation. These types have 2 types of intermediacy on each, probability and usuality for modalization and obligation and inclination for modulation.